Sipunculans along the Aegean coast of Turkey - Açik, Sermin (Zootaxa, 2008)
Faunistical analysis of benthic samples collected from different depths and biotopes (0–195 m) at 108 stations along the Turkish Aegean coast yielded 11 species and 5 subspecies of Sipuncula. Two species (Phascolion (Isomya) tuberculosum and Aspidosiphon (Aspidosiphon) misakiensis) are new to the eastern Mediterranean fauna and 8 species are new to the Turkish fauna. Onchnesoma steenstrupii steenstrupii has the highest dominance and frequency index values in the study area. Aspidosiphon (Aspidosiphon) elegans and Apionsoma (Apionsoma) misakianum are alien species. Of the biotopes examined, muddy sand was characterized by the highest number of species and specimens, whereas sponges and coralligenous substrata were characterized by the lowest number of species and specimens. The biometrical and reproductive features of the species are presented and discussed.